2016
DOI: 10.5897/ijmms2015.1207
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychoactive substance use among registered commercial motorcycle operators in Kano, North Western Nigeria: A community study

Abstract: The present study was carried out in the most populated city in Northern Nigeria that is believed to have the highest number of commercial motorcyclists and highest prevalence of psychoactive substance use in the country. Research on psychoactive substance use among motorcycle operators in Northern Nigeria is limited, despite the high level of morbidity these substances cause to them. This study aimed to study the prevalence of psychoactive substance use among motorcycle operators in Kano, North western Nigeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Alcohol consumption, on the other hand, continues to be a common behavior among MTDs, with a prevalence ranging from 29.5% to 69% [7] [8] [10] [14]. The results of a study in Nigeria showed that tobacco consumption was significantly higher than that reported for other drugs such as cannabis [15]. By the way, hypotheses have been put forward as to the neurological and/or physiological effects of toxic substances in tobacco that interfere with driving [16].…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol consumption, on the other hand, continues to be a common behavior among MTDs, with a prevalence ranging from 29.5% to 69% [7] [8] [10] [14]. The results of a study in Nigeria showed that tobacco consumption was significantly higher than that reported for other drugs such as cannabis [15]. By the way, hypotheses have been put forward as to the neurological and/or physiological effects of toxic substances in tobacco that interfere with driving [16].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, in spite of the fact that the extent of psychoactive substance use among the world population has remained stable over the past four years; over 29 million people are estimated to suffer from psychoactive prevalence of psychoactive substance use which accounts for 19.3% (Gudaji and Habib, 2016).…”
Section: Introductionmentioning
confidence: 99%